Study designs in biomarker research - Ahmadian, Robab; Ocakoglu, Gokhan (The European Research Journal, 2017)
In order to advances in technology, nowadays science is facing to a large variety of biomarkers. Issues of selecting appropriate study design for biomarkers, facing with a large number of biomarkers, multiple biomarkers, and usefulness of a new biomarker the today is more complicated. Current study is an overview of the issues discussed in studies of biomarkers.